Exploring Communication Skills and Student Learning Outcomes through Student Facilitators and Explaining (SFAE) Learning Model - Yulia Pramusinta; Aprilia Yustika Dewi (Universitas Pendidikan Ganesha, 2023)
The low learning outcomes and communication skills of students in elementary schools still need to be solved in education in Indonesia. At the same time, basic education in the 21st century requires students to be able to collaborate and be able to communicate well. These two skills are needed in the learning process so that learning can run effectively and efficiently. This research aims to analyze students' communication skills and good learning outcomes through the student facilitator and explaining (SFAE) method. This study used a quantitative research type with a pre-experimental design with one pretest-posttest group. The research subjects were grade 2 students, totaling 34 students. Data collection methods using observation techniques, interviews, thematic learning achievement tests, and communication skills questionnaires. The research instrument used a student communication skills questionnaire which totaled 20 question items and a cognitive learning achievement test which totaled 27 multiple-choice questions with a range of C4-C5. Data analysis in this study used the normality test and paired sample t-test. The results showed that there was a significant influence between students' communication skills and student learning outcomes. Communication skills and student learning outcomes can be well explored through the student facilitator and explaining (SFAE) model.